ARTISTIC EXPRESSION OF TRAUMATIC REALISM IN EDWIDGE DANTICAT'S FICTION (Web of Teachers: Inderscience Research, 2025)
This article offers an in-depth analysis of the artistic expression of traumatic realism in Edwidge Danticat's work, “The Dew Breaker”. The article highlights the ruthless activities of the protagonist during the dictatorship regime and impact of these activities on his current life, showing the echo of psychological trauma on both individual and societal levels. The study examines how traumas are represented in literature through psychoanalytic, postcolonial, and socio-cultural approaches. In addition, the contradictions between personal and collective memory, the past and the present, and the artistic expression of traumatic experiences are scrutinized in detail. Through the dynamic portrayal of the protagonist in Danticat's work, the concept of trauma is deeply revealed, and its role in literary art is highlighted.